Religious and cultural foundations of hospitality in the Islamic and Japanese traditions: a preliminary comparison - Kushimoto, Hiroko (American Scientific Publishers, 2017)
The term "hospitality" is increasingly used as common styles of commercial service without consideration of different understandings in each culture and society. Understanding the differences in the religious or cultural notion of hospitality is important in increasing the quality of hospitality industry, however, there are only limited studies on the cultural ideas of hospitality. Therefore this article aims to identify religious and cultural foundations of the concept of hospitality in Islamic and Japanese tradition, as a preliminary study for comparison of hospitality cultures. This article first discussed the Islamic ideas of hospitality based on the authentic texts of Islam, namely Qur'an, Hadith and Ihya ‘Ulum al-Din written by al-Ghazali (d.1111). The analysis of its feature focuses on three elements; (1) relationship between hosts and guests, (2) the concept of generosity, and (3) gender roles. Then these three elements will be compared to the Japanese counterpart based on the texts explained Japanese roots of hospitality in the tea ceremony. The major differences are found in the place of God in the meaning of providing hospitality, charitable aspects of hospitality, its connection to daily life, and the women's roles as providers of hospitality, while similarity was found in the importance of hospitality, virtue of modesty and the idea of collaboration between guests and hosts to create pleasant moment. Understanding such similarities and differences in the ideas of hospitality will help the tourism industry in both Muslim countries and Japan to increase the quality of hospitality.